Metabolic dysfunction associated fatty liver disease and type 2 diabetes: pathophysiological links, epidemiological trends, and clinical implications - Mohiuddin, Mohammad Sarif; Neha, Noushin Tabassum; Mahir, Jawad Ul Karim; Shakib, Fardin Al Fahad; Alam, Md. Ashraful; Wahiduzzaman, Md.; Barua, Rashu; Shimu, Shakila Jahan; Rahman, Mahbubur; Hossain, Md. Rafin; Shariare, Mohammad Hossain; Mohib, Mohammad Mohabbulla; et al. (Frontiers in Endocrinology, 2025)
Metabolic dysfunction-associated steatotic liver disease (MASLD), previously known as non-alcoholic fatty liver disease (NAFLD), has recently been recognized as a public health issue because it is closely linked to metabolic disorders, including type 2 diabetes mellitus (T2DM). This review aims to discuss the bidirectional relationship between MASLD and T2DM and the similarities in their pathophysiology, which include insulin resistance (IR), lipogenesis, inflammation, and alterations in the gut microbiota. The incidence of MASLD has increased concomitantly with the obesity and diabetes pandemic, and more than 60% of individuals with T2DM have liver steatosis. The metabolic dysfunction is followed by adipokines, inflammatory mediators like TNF-α, IL-6, and oxidative stress, which worsen NAFLD and lead to T2DM. Since MASLD is usually asymptomatic in its early stages, it is important to screen high-risk populations such as obese and metabolic syndrome patients to enable them to start treatment early. Lifestyle changes, including changes in diet, weight loss, and increased physical activity, are currently the mainstay of treatment for MASLD; however, the potential of new pharmacological approaches that act on insulin signaling, hepatic lipid metabolism, and inflammation to improve treatment is encouraging. Although the role of MASLD in the pathogenesis of T2DM has been well-documented, there are issues with standardizing the diagnostic criteria and the availability of effective treatments. This is because the multidisciplinary management of metabolic diseases needs hepatology, endocrinology, and public health measures to prevent a global epidemic. More studies are required to fully understand the underlying molecular mechanisms of MASLD-T2DM and search for specific treatment for high-risk patients.